Characterization of commercial wheat flour sold in Myanmar and its application in the fried chicken - Kyaw, Ei Mon Mon; Therdthai, Nantawan; Jagnchud, Kamolwan; Jangchud, Anuvat (Food and Applied Bioscience Journal, 2017)
Fried chicken has been the most popular fast food in worldwide. The demand was yearly increased due to the change of lifestyle. However, wheat flour that is one of major ingredients to develop dry mix for fried chicken has to be imported. Its cost became expensive. Therefore, this project aimed to determine Myanmar wheat flour quality and to investigate its potential to use for making the dry mix for fried chicken. Three Myanmar flours (flour A, B and C) were selected from the most popular brands. L*, a* and b* of all flours were in the range of 93.06 – 94.58, 0.47 – 0.69, and 7.82 – 9.29, respectively. Their moisture content, fiber content, fat content, ash content and carbohydrate content were 11.79-12.85%, 0.73–2.74%, 0.86–1.18%, 0.21–0.43% and 50.27–69.08%, respectively. Protein contents of flour A, B and C were 15.23%, 35.22% and 31.12% respectively. For pasting properties, flour B and C had significantly higher peak viscosity, trough, break down, final viscosity and set back than did flour A. Variation in those properties did not affect %pick up and cooking loss (P>0.05). However, it affected fat content of fried chicken crust significantly (P<0.05). The fried chicken crust fromflour C had the least fat content (27.12%). Hardness of the fried chicken with flour A, B and C were 13.37 N, 12.80 N and 7.73 N, respectively. Among those flours, flour A and flour B could produce the fried chicken with the highest overall liking score.